2020
DOI: 10.1515/epoly-2020-0068
|View full text |Cite
|
Sign up to set email alerts
|

Structural design toward functional materials by electrospinning: A review

Abstract: Electrospinning as one of the most versatile technologies have attracted a lot of scientists’ interests in past decades due to its great diversity of fabricating nanofibers featuring high aspect ratio, large specific surface area, flexibility, structural abundance, and surface functionality. Remarkable progress has been made in terms of the versatile structures of electrospun fibers and great functionalities to enable a broad spectrum of applications. In this article, the electrospun fibers with different stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(81 citation statements)
references
References 235 publications
2
79
0
Order By: Relevance
“…With the continuous research of related scholars, the application of electrospinning nanofibers has become more and more extensive. In addition to playing a role in the field of biomedicine (drug delivery [ 150 , 151 , 152 ], tissue engineering [ 153 ] and wound dressings), it also plays a pivotal position in environmental protection (air filtration, water treatment), energy and chemical industries (light-emitting device, solar cell and supercapacitor) and other fields [ 154 , 155 ]. Fiber materials with unique structures and characteristics arranged by electrospinning have been generally utilized in different fields ( Figure 9 ).…”
Section: Electrospun Nanofibers In Wound Dressingmentioning
confidence: 99%
“…With the continuous research of related scholars, the application of electrospinning nanofibers has become more and more extensive. In addition to playing a role in the field of biomedicine (drug delivery [ 150 , 151 , 152 ], tissue engineering [ 153 ] and wound dressings), it also plays a pivotal position in environmental protection (air filtration, water treatment), energy and chemical industries (light-emitting device, solar cell and supercapacitor) and other fields [ 154 , 155 ]. Fiber materials with unique structures and characteristics arranged by electrospinning have been generally utilized in different fields ( Figure 9 ).…”
Section: Electrospun Nanofibers In Wound Dressingmentioning
confidence: 99%
“…The diameter, morphology, and structure of the electrospun fibers are key factors that need to be controlled for practical applications [88,89]. They depend on a multitude of parameters related to the solution, setup and electrospinning process [90][91][92][93][94].…”
Section: Polymer-assisted Synthesis Of Nanofibersmentioning
confidence: 99%
“…[ 9 ] Studies have demonstrated that the structure and properties of the reinforcing nanofibers have a critical influence on the properties of the composite. [ 11,12 ] In particular, nanofiber diameter is a key factor affecting the performance of nanofiber‐reinforced composites. [ 13–15 ] Many studies have demonstrated the effect of fiber diameter on the mechanical properties of electrospun fibers.…”
Section: Introductionmentioning
confidence: 99%